Capitalism after Satoshi: Blockchains, dehierarchicalisation, innovation policy, and the regulatory state. Issue 2 (4th October 2019) - Berg, Chris; Davidson, Sinclair; Potts, Jason
Abstract : Purpose: The purpose of this paper is to explore the long-run economic structure and economic policy consequences of wide-spread blockchain adoption. Design/methodology/approach: The approach uses institutional, organisational and evolutionary economic theory to predict consequences of blockchain innovation for economic structure (dehierarchicalisation) and then to further predict the effect of that structural change on the demand for economic policy. Findings: The paper makes two key predictions. First, that blockchain adoption will cause both market disintermediation and organisational dehierarchicalisation. And second, that these structural changes will unwind some of the rationale for economic policy developed through the twentieth century that sought to control the effects of market power and organisational hierarchy. Research limitations/implications: The core implication that the theoretical prediction made in this paper is that wide-spread blockchain technology adoption could reduce the need for counter-veiling economic policy, and therefore limiting the role of government. Originality/value: The paper takes a standard prediction made about blockchain adoption, namely disintermediation (or growth of markets), and extends it to point out that the same effect will occur to organisations. It then notes that much of the rationale for economic policy, and especially industry and regulatory policy through the twentieth century was justified in order to control economic power created by hierarchical organisations. The surprising implication, then, is that blockchain adoption weakens the rationale for such economic policy. This reveals the long-run relationship between digital technological innovation and the regulatory state.